A Review: Structure and Synthesis of Perovskite as Lithium-Ion Battery (LIB) Material - Miranti Maya Sylvani; Ferry Purwanto; Jumiati; Elfrida Roulina Simanjuntak; Sari Namarito Simarmata; Rendy Muhamad Iqbal; Riandy Putra; Rokiy Alfanaar; Siti Unvaresi Misonia Beladona (Program Studi Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Palangka Raya, 2023)
Lithium-ion battery (Li-ion battery or LIB) has gained significant attention as a highly promising power source. It offers excellent energy and power density profiles, along with other desirable properties such as no memory effect and long-lasting power capabilities. This has made Li-ion battery technology highly sought after in the energy industry and electronic devices. Perovskite materials have emerged as one of the non-precious metal-based materials that have attracted considerable interest in recent decades. Perovskites are highly regarded due to their remarkable properties and their potential applications in electrochemical energy devices. They possess excellent physical and chemical characteristics that make them suitable for use as electrode materials in rechargeable lithium-ion batteries.